THE IMPACT OF MENTAL HEALTH DISORDERS ON PHYSICAL DISEASE RISKS: A COMPREHENSIVE REVIEW - Isdianto, Andik; Al Indunissy, Nuruddin; Fitrianti , Novariza (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study evaluates the impact of mental health disorders such as stress, anxiety, and depression on the risk of various physical illnesses, including cardiovascular diseases, type 2 diabetes, obesity, immune system disorders, respiratory conditions, skin disorders, digestive ailments, and osteoporosis. Employing a literature review methodology, the research analyzed data from previous studies, uncovering that mental disorders elevate the risk of cardiovascular diseases through oxidative stress and systemic inflammation mechanisms. The link between stress and glycemic dysregulation in type 2 diabetes highlights a trend towards increased insulin resistance. Depression, closely associated with obesity, is often exacerbated by unhealthy eating habits used as coping mechanisms. Chronic stress-induced immune system disorders result in decreased immune responses, while respiratory issues such as asthma are intensified by increased anxiety. Skin conditions like psoriasis and eczema frequently worsen due to psychological stress. In digestive disorders such as irritable bowel syndrome, stress contributes to more severe symptoms, and osteoporosis is similarly affected by chronic stress impacting bone metabolism. These findings affirm the critical importance of routine mental health screenings and the integration of effective public health interventions in overall health management, as exemplified by the Rehab Hati Foundation. Public health programs that enhance mental health can aid in preventing and managing physical illnesses, improving life quality, and reducing overall health burdens. The conclusion highlights the essential role of effective mental health management as both a preventive and therapeutic strategy.